Variability of water flow in the hyporheic corridor: A case study of the Warta Valley in Poznań - Okońska, Monika; Wolny, Filip (Quaestiones Geographicae, 2025)
The relationship between surface water (SW) and groundwater (GW) is most evident in river valleys, where GW typically lies at shallow depths beneath the surface. The nature of this relationship can change dynamically over time, depending on various factors such as water levels, landform features, meteorological and hydrogeological conditions and the initial retention capacity of the catchment area. Additionally, in meandering rivers, GW may flow through the alluvium of the meander along the river channel within a hyporheic corridor, following the hydraulic gradient and thus shortening the flow path. This study presents the results of observations of river and GW levels conducted at the hydrological station of Adam Mickiewicz University (AMU), located in the Warta Valley in Poznań. The main objective was to determine the position of the GW table relative to the river water level and to analyse the variability of GW flow in the study area. The findings confirmed the functioning of the hyporheic corridor in the studied meander of the Warta River.